161k views
0 votes
If g(x) = 5x2^2 - 10x + 9 and h(x) = -3x3^3+ 5x - 6, find g(x) - h(x)?

A)
3x3 + 5x2 +15x + 15
3x3 - 5x2 - 15x + 15
C)
-3x3 + 5x2 - 5x + 3
D)
3x3 + 5x2 - 15x + 15

User HumeNi
by
5.4k points

2 Answers

2 votes

Answer: B

Step-by-step explanation: Hope it helps :)

User Adrian Nowicki
by
6.2k points
3 votes

Answer:

B)
g(x) - h(x) =  3x^3 - 5x^2 - 15x + 15

Explanation:

Here, the given functions are:


g(x) = 5x^2- 10x + 9 \\h(x) = -3x^3+ 5x - 6

Now, g(x) - h(x) is :


(5x^2- 10x + 9)  - ( -3x^3+ 5x - 6)\\= 5x^2- 10x + 9 + 3x^3 - 5x + 6\\= 3x ^3 + 5x ^2+  (-10 x - 5 x) + (9 + 6)\\= 3x^3 - 5x^2 - 15x + 15


(5x^2- 10x + 9)  - ( -3x^3+ 5x - 6) =  3x^3 - 5x^2 - 15x + 15

B) Hence,
g(x) - h(x) =  3x^3 - 5x^2 - 15x + 15

User Racc
by
6.3k points